A windowing and mapping strategy for gear tooth fault detection of a planetary gearbox. (1st December 2016) - Liang, Xihui; Zuo, Ming J.; Liu, Libin
Abstract: When there is a single cracked tooth in a planet gear, the cracked tooth is enmeshed for very short time duration in comparison to the total time of a full revolution of the planet gear. The fault symptom generated by the single cracked tooth may be very weak. This study aims to develop a windowing and mapping strategy to interpret the vibration signal of a planetary gear at the tooth level. The fault symptoms generated by a single cracked tooth of the planet gear of interest can be extracted. The health condition of the planet gear can be assessed by comparing the differences among the signals of all teeth of the planet gear. The proposed windowing and mapping strategy is tested with both simulated vibration signals and experimental vibration signals. The tooth signals can be successfully decomposed and a single tooth fault on a planet gear can be effectively detected. Highlights: A windowing and mapping strategy is proposed for gear tooth fault detection. A numerical method is proposed to find the optimal window positions. The proposed method is able to detect a tooth crack on a single planet gear.